Efficiency and Tolerance of Misoprostol versus Oxytocin in the Active Management of the Third Period of Delivery at the University Maternity Porto-Novo, Benin - OGOUDJOBI, CHRISTIANE; OGOUDJOBI, OGOURINDÉ MATHIEU; LOKOSSOU, Mègnissè Sèna H. S. (My University, 2018)
Objective: To assess the efficiency and tolerance of misoprostol versus oxytocin in Active Management of the Third Period of Childbirth. Framework and Method of Study: The study was carried out at the Porto-Novo university maternity in Benin. The hospital is level 3. He acted in a randomized clinical trial with a descriptive and comparative aim referred from 1st January 2017 to 31st December 2017. We included all eligible women in labor in the delivery room during the study period and at that gestational age was greater than or equal to 37 weeks of amenorrhea, delivery was done through vaginal birth and delivered with a live birth and agreed to participate in the study. The cases eligible by order of admission were grouped in blocks of two, “Misoprostol” and “Oxytocin” corresponding to the Active Management of the Third Period of delivery. The data collected were captured and analyzed using the SPSS version 20 software. For the comparison of the results, we used the chi-square statistical test and the difference was assumed to be statistically significant for a p ≤ 0.05. The confidentiality of parturient was respected. Results: we recorded 1234 of which were delivered via vaginal birth. The Active Management of the Third Period of Delivery was carried out in 1202 parturients. According to our inclusion criteria, 892 parturients were retained for the study, of which 446 for each group. The average age of parturients was 26.94 ± 5.65 years. Almost pregnancies were mono-fetal (95.7% vs. 93.5%). The average time to expel the placenta after utero-tonic administration was 4.05 ± 0.27 min in the “Misoprostol” group versus 3.82 ± 0.52 min in the “Oxytocin” group (p > 0.05). We had only 9 cases of placental retention in the group “Misoprostol” versus 5 cases in the “Oxytocin” group. Most of the parturients had blood loss less than 500 ml (96.2% vs. 96.6%). The frequency of delivery hemorrhage was 3.8% in the “Misoprostol” group versus 3.4% in the “Oxytocin” group. The mean blood volume lost was 284.33l ± 13.31 ml in the “Misoprostol” group versus 225.94 ± 21.52 ml in the “oxytocin” group. Maternal prognosis was generally good in both groups. Conclusion: Misoprostol may be an alternative in Active Management of the Third Period of Delivery especially in developing countries where the cold chain is often lacking
Keywords: Misoprostol; Oxytocin; Delivery